The Relationship between Hemodialysis Adequacy and Quality of Life in Chronic Kidney Disease (CKD) Patients in the Hemodialysis Room at Prof.Dr.I.G.N.G Ngoerah Hospital - Muliawati Ni Kadek; Sudiarta I Made; Citrawati Ni Ketut (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2024)
Introduction: Hemodialysis (HD) therapy that lasts a lifetime should ideally have a positive impact in the form of improving the patient's quality of life, however, based on research results, poor quality of life in kidney failure patients undergoing hemodialysis still occurs. One of the factors that affects the quality of life in CKD patients is HD adequacy. Objectives:  This study was to determine the relationship between hemodialysis adequacy and quality of life in Chronic Kidney Disease (CKD) patients. Methods: The research method used is descriptive correlational with a cross-sectional approach. The total sample was 91 respondents selected using a purposive sampling technique. HD adequacy instrument by inputting data on the HD machine which includes age, height, dry body weight, and setting the Kt/V value adequacy target on the machine greater than 1.8 (for HD 2x/week) while the Quality-of-Life Instrument uses KDQOL-SF which consists of 36 questions. The analytical test used in this research is the Spearman rank correlation test. Results:  The HD adequacy results of the majority of respondents were inadequate, namely 58 respondents (63.7%), the majority's quality of life was in the moderate category, namely 68 respondents (74.7%), the results of data analysis showed that there was a significant relationship between HD adequacy and quality of life. In CKD patients (p-value 0.000) with a correlation coefficient of 0.509.  Discussion:  Achievement of HD adequacy is one of the factors that play a role in improving the quality of life of patients, so it is an important indicator in evaluating the implementation of the HD process.